Variations of Bioactive Phytochemicals and Antioxidant Capacity of Navel Orange Peel in Response to Different Drying Methods - Chunling Lai; Yan Liang; Linyan Zhang; Jiangjiang Huang; Kumaravel Kaliaperumal; Yueming Jiang; Jun Zhang (MDPI AG, 2022)
The effects of five different drying methods, namely, freeze drying (FD), shade drying (SD), hot-air oven drying at 50 °C (OD50), 70 °C (OD70), and microwave drying (MD) on the bioactive phytochemicals and antioxidant capacity of navel orange peel were assessed and comprehensively discussed in detail. Compared with other drying methods, MD-treated peel contained the lowest total phenolic content (TPC) and total flavonoid content (TFC). The peel subjected to OD70 treatment was superior in TPC relative to other treatments and the highest TFC was found in the peels treated with FD. HPLC analysis identified thirteen flavonoids involving three flavanone glycosides (FGs) and ten polymethoxyflavones (PMFs) in navel orange peel and revealed that PMFs in peel were stable under all these drying methods, whereas the three major FGs (narirutin, hesperidin, and didymin) in peel significantly degraded in response to MD treatment. The peels subjected to OD50/OD70 treatments had the most potent antioxidant capacity when compared to other drying methods. Furthermore, Pearson's correlation analysis was performed. The results revealed here allow us to recommend the use of OD50 or OD70 for the drying of orange peel, both of which help the maintenance of bioactive compounds in the peel and improve its antioxidant capacity.